EFFECT OF SOLVENT TYPE ON THE ANTIOXIDANT PROPERTIES OF HYDROQUINONE - Radhi, Mustafa Jassim (Tanjungpura University, 2026)
While hydroquinone (HQ) is a vital antioxidant, the precise mechanisms governing its activity—specifically HAT, SET-PT, and SPLET—and their dependencies on solvent environments remain a subject of debate. Standard implicit solvent models often fail to accurately predict these behaviors. In this study, the antioxidant mechanisms of hydroquinone in water, ethanol, and acetone were investigated using two computational approaches: a standard implicit model (PCM) and a hybrid explicit-implicit model. Results from the initial implicit model were found to be inconsistent with experimental observations, incorrectly identifying SET-PT as the dominant mechanism across all media and suggesting acetone as the most favorable solvent (∆G = 585.60 kJ/mol). However, the hybrid model, which accounts for direct solvent participation in proton transfer, revealed that the SPLET mechanism is the dominant pathway in protic solvents. The established order of antioxidant activity is: water (SPLET, 379.7 kJ/mol) > ethanol (SPLET, 479.4 kJ/mol) > acetone (SET-PT, 585.6 kJ/mol). These findings confirm that acetone is the optimal solvent for maintaining hydroquinone stability and underscore the critical necessity of employing hybrid models when simulating proton-coupled electron transfer reactions in protic environments.